Tolerance in Inquiry-Based Learning: Building Harmony and Solidarity in Students - Abdul Wahid; D.Y.P. Sugiharto; S Samsudi; H Haryono (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2018)
This study aims to reveal how inquiry-based learning can be used as a strategy in building harmony and solidarity which, in turn, can instill tolerance values in students. It is a qualitative research involving Sekolah Alam Ungaran in Semarang Regency as its subject of study. The study employs in-depth interview, observation, and documentation. It uses triangulation of resources and methods to ensure data validity. Meanwhile, data analysis refers to the Miles and Huberman technique. The study finds that the tolerance values in inquiry-based learning in Sekolah Alam Ungaran are built through three types of activities: (1) self-development through routine activities, spontaneous activities, exemplary and conditioning; (2) integration into materials or courses, and (3) formation of school culture. Later, these findings are designed to be a model of inquiry-based learning to build harmony and solidarity in students.